Impact of Dividend Announcements of Banks on Stock Returns and the Determinants of Dividend Policy - B. G., Poornima; Morudkar, Vassanti; Reddy, Y. V. (Indian Journal of Finance, 2019)
The study attempted to examine and compare the impact of dividend announcements on the stock returns of the public and private sector banking companies of the Indian share market and also examined the factors that determined the dividend policy of the banking companies using event study and panel data methodology, respectively. A sample of 38 companies listed on the BSE Bankex index of Bombay Stock Exchange (BSE), which made 172 dividend announcements for the period of 2011-2015, were considered. The study found that dividend announcements of public sector banks had a negative impact on stock returns, while the dividend announcements of private sector banks had a positive impact on stock returns. The examination of determinants of dividend policy revealed that in case of public sector banks, only size had a significant effect on the current year's dividend payout ratio, while in case of private sector banks, leverage, profitability, risk, and last year's dividend had a significant impact on the current year's dividend payout ratio.